Urbanistikos paveldo išsaugojimo teisinės prielaidos Lietuvoje - Jurevičienė, Jūratė (Journal of Architecture and Urbanism, 2009)
Legal preconditions of urban heritage preservation in Lithuania The paper discusses urgent problems of urban heritage assesment and treatment in Lithuania today. Contradictions in the system of listing, lack of fundamental investigations, indeterminate responsibility of authorities, inadequate role of local communities are revealed as the basic factors of low efficiency of urban heritage preservation. The most efficient means of urban heritage preservation are revealed in protected national and regional parks. Historic towns and villages of these areas remain more authentic than registered urban heritage sites in the other territories of Lithuania. The initiative of local administrations could also be considered as one of the most important factors in urban heritage preservation. Scandinavian experience in the protection of urban heritage reveals the importance of local inhabitants in the processes of historic town preservation. Recent international documents on cultural heritage protection and changes in the Lithuanian urban planning system enable perfection of urban heritage preservation. The launched reimbursement of expenses for restoration works in Lithuania shows positive changes in this field. Article in Lithuanian. Santrauka. Nagrinėjamos dabarties Lietuvoje susiklosčiusios teisinės paskatos ir kliūtys išsaugoti urbanistikos paveldą. Analizuojami Lietuvos įstatymai ir įstatymų įgyvendinamieji dokumentai, reglamentuojantys urbanistikos paveldo vietovių apsaugą kultūros paveldo apskaitos bei teritorijų planavimo lygmenyse. Siekiama atskleisti urbanistinių darinių vertingųjų savybių išsaugojimo teisinių nuostatų veiksmingumą. Atskleidžiami teisiniai trukdžiai ir paskatos gyventojams dalyvauti istorinių miestų ir miestelių kultūrinės vertės išsaugojimo procesuose. Reikšminiai žodžiai: urbanistikos paveldas, kultūros paveldo apskaita, teritorijų planavimas, visuomenė. First Published online: 21 May 2013